Myiasis cases and their treatments in cows, sheep and goats in Elazig province - Saki, CE; Özer, E (Tubitak Scientific & Technological Research Council Turkey, 1999)
This study was carried out on cows, sheep and goats in Salkaya Village, Kovancilar, Baskil and Sivrice towns and in Eiazig during 1994 and 1995. Fifty two myiasis cases were detected throughout the study. Forty seven (90.38%) and 5 (9.62%) of the cases were determined in sheep and cows respectively, no myiasis case was encountered in goats. Twenty two (42.32%) of the cases were seen in June during 1994 and 1995, 10 (19.23%) in May, 9 (17.31%) in July, 8 (15.38%) in September and 3 (5.77%) in August. Identification of the collected larvae showed that 51 (98.08%) and 1 (1.92%) of the wounds were caused by W. magnifica and L. sericata respectively The wounds, cleared of necrotic tissues and rinsed with the suitable antiseptics before the spraying with negusant, were fully cured.
Keywords: cow; sheep; goat; external myiasis; treatment